Transition analysis of the non-OT G2 stiff fluid spike solution. (17th December 2021) - Lim, W C; Moughal, M Z A
Abstract: We use the technique developed in Moughal's doctoral thesis to analyse the joint spike transition, revealing new groups of worldlines which undergo distinct transitions, and correcting misconceptions about spikes.